Pengembangan Model Pembelajaran Logika Matematika melalui Bermain Menggunakan Media Berbahan Alam di TK Negeri I Dharma Wanita Desa Eti, Kabupaten SBB - Lisa Maarce Sahetapy; Heldy Ivana Laturake; Huberta Yempormasse (Jurnal Pendidikan dan Sastra Inggris, 2025)
The research purpose is for developing effective mathematical logic learning model to early childhood through play activities using natural material media. This model is designed to stimulate children's logical thinking and mathematical abilities by utilizing natural materials such as shells, seeds, banana fronds, leaves, and stones as concrete and engaging learning media. Function of those materials is hope for enhancing children's interest and motivation in learning mathematics while considering their cognitive development stages comprehensively. The research method employed is a development research approach with stages of design, validation, and trial of the developed learning model. Validation is conducted by experts in education and early childhood learning to assess the feasibility of the model, while trials involve teachers and students at TK Negeri 1 Dharma Wanita Desa Eti, SBB Regency. The results indicate that this learning model is valid and practical for use, and it positively influences the improvement of children's mathematical logic abilities. These findings provide significant contributions for make developing of enjoyable also effective mathematics learning in early childhood education with a play-based approach using natural media. Teachers and educators can adopt this model to create an interactive learning environment that aligns with children's developmental characteristics. Additionally, the use of natural material media also supports children's awareness of their surrounding environment. Therefore, this model is a viable alternative to be developed and implemented in early childhood education.